Development of Jump Number Play Media in Stimulating Children's Cognitive Development - Alqolida Munasti; Shofiyanti Nur Zuama; Hamzia Marie; Durrotunnisa Durrotunnisa (FKIP - Universitas Riau, 2026)
The problem in this study lies in the cognitive ability of children in recognizing the symbols of numbers 1-20, which has not developed as expected. This study aims to determine the development of Jump Number Play (JNP) media in stimulating children's cognition. This study used Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research subjects consisted of 16 children, comprising 7 girls and 9 boys in the odd semester of the 2025/2026 academic year. Data were collected through observation and interviews with homeroom teachers. The final stage of expert validation of the JNP media obtained 100% and media experts obtained 97.05%. These results show that the JNP media is very valid in stimulating children's cognitive development in recognizing the symbols for numbers 1-20. The results of observations and children's responses after playing with the JNP media, in terms of recognizing the symbols for numbers 1-20, showed that there were 2 children (12.50%) in the BSB category, 12 children (75.00%) in the BSH category, 2 children (12.50%) in the MB category, and no children in the BB category. In terms of naming number symbols 1-20, there were 2 children (12.50%) in the BSB category, 12 children.